Demographics and sexual characteristics of sex-enhancing medication users: Study of a web-based cross-sectional sample of sexually active men - Abul-Fotouh Ahmed (Taylor & Francis Group, 2017)
Objectives: To evaluate the frequency of sex-enhancing medications (S-EM) use and to investigate the demographics and sexual characteristics of the S-EM users amongst a Saudi Arabian male population. Subjects and methods: A cross-sectional sample of 1176 Saudi Arabian men was recruited using a web-based survey between 1 January and 1 April 2015. The survey included multiple open and closed questions to assess the frequency of S-EM use; and demographics, clinical, and sexual characteristics of S-EM users, as well as their perceptions of S-EM. Results: Amongst the participants, 1008 were sexually active and included in the data analysis. Of the sexually active participants, 402 (39.9%) reported S-EM use in the form of herbal or phosphodiesterase type 5 inhibitors at some time in their lives. Comparing S-EM users with S-EM non-users, the S-EM users had a number of demographic and sexual characteristics including: higher education level, higher income, smoking, more than one sexual partner, longer sexual activity duration, higher frequency of sexual intercourse, and lower sexual satisfaction level. Most of the S-EM users (82.1%) bought S-EM without a medical prescription and 62.5% had used them recreationally. In all, 52% of respondents used S-EM to treat ED and 69% of those who used it recreationally reported enhancement of erection with S-EM usage. Conclusions: Demographic and sexual characteristics of S-EM users and the attitude of the users towards the S-EM were identified amongst a Saudi Arabian male population. Keywords: Characteristics, Phosphodiesterase type 5 inhibitors, Sex-enhancing medication use